Cyclo (Pro-Tyr) upregulates GmPOD53L to enhance soybean resistance to cyst nematode (Heterodera glycines Ichinohe) - Wang, Hui; Li, Yuanjie; Wang, Xudong; Liu, Shumei; Fan, Fengjiao; Qi, Songjie; Wang, Min; Jia, Yubo; Chen, Qiumin; Duan, Yuxi; Liu, Chen (Frontiers in Plant Science, 2025)
The soybean cyst nematode (Heterodera glycines Ichinohe, SCN) poses a significant threat to soybean yield, often leading to total crop failure in heavily infested areas. Identifying key resistance genes is essential for enhancing soybean resistance to SCN. This study demonstrates that pre-treatment with a bacterial extract, CPT, can enhance SCN resistance in soybean roots by increasing lignin content and peroxidase (POD) activity. Further investigation revealed that the Class III POD gene GmPOD53L (Glyma.02G171600) is upregulated under SCN stress, correlating with increased peroxidase activity and lignin content. Overexpression of GmPOD53L significantly bolstered SCN resistance, as evidenced by reduced SCN numbers, slowed SCN development, heightened lignin deposition, and elevated POD activity. Conversely, silencing GmPOD53L had the opposite effect. These findings suggest that GmPOD53L positively regulates SCN stress by enhancing lignin content and POD activity, thereby inhibiting SCN invasion and development. This study identifies GmPOD53L as a candidate gene for soybean breeding programs aimed at improving SCN resistance and provides a theoretical foundation for the development of related bio-based seed coatings and SCN-resistant breeding efforts.